Allelic and genotypic frequencies of NAT2, CYP2E1, and AADAC genes in a cohort of Peruvian tuberculosis patients. Issue 10 (12th September 2021) - Levano, Kelly S.; Jaramillo‐Valverde, Luis; Tarazona, David D.; Sanchez, Cesar; Capristano, Silvia; Vásquez‐Loarte, Tania; Solari, Lely; Mendoza‐Ticona, Alberto; Soto, Alonso; Rojas, Christian; Zegarra‐Chapoñan, Roberto; Guio, Heinner
Abstract: Background: We determined the frequency of genetic polymorphisms in three anti‐TB drug metabolic proteins previously reported: N ‐acetyltransferase 2 ( NAT2 ), cytochrome P450 2E1 ( CYP2E1 ), and arylacetamide deacetylase ( AADAC ) within a Peruvian population in a cohort of TB patients. Methods: We genotyped SNPs rs1041983, rs1801280, rs1799929, rs1799930, rs1208, and rs1799931 for NAT2 ; rs3813867 and rs2031920 for CYP2E1 ; and rs1803155 for AADAC in 395 participants completed their antituberculosis treatment. Results: Seventy‐four percent of the participants are carriers of slow metabolizer genotypes: NAT2*5, NAT2*6, and NAT2*7, which increase the sensitivity of INH at low doses and increase the risk of drug‐induced liver injuries. Sixty‐four percent are homozygous for the wild‐type CYP2E1*1A allele, which could increase the risk of hepatotoxicity. However, 16% had a NAT2 fast metabolizer phenotype which could increase the risk of acquiring resistance to INH, thereby increasing the risk of multidrug‐resistant (MDR) or treatment failure. The frequency of rs1803155 ( AADAC*2 allele) was higher (99.9%) in Peruvians than in European American, African American, Japanese, and Korean populations. Conclusions: This high prevalence of slow metabolizers for isoniazid in the Peruvian population should be further studied and considered to help individualize drug regimens, especially in countries with a great genetic diversity like Peru. These data will help the Peruvian National Tuberculosis Control Program develop new strategies for therapies. Abstract : High prevalence of slow metabolizers for isoniazid in the Peruvian population should be further studied and considered to help individualize drug regimens, especially in countries with a great genetic diversity like Peru.